PERFORMANCE ANALYSIS OF NATIONAL TABLE TENNIS ATHLETES: FACTORS AFFECTING ACHIEVEMENT - Saragih, Devi Uliani Br; Priscilia, Anggie; Suwandira, Suwandira; Lubis, Ferdi Hasan; Pratama, Muhammad Yudha; Hafiz, Muhammad; Manalu, Nimrot; Padli, Zen (Journal Physical Education, Health and Recreation, 2025)
The purpose of this study is to evaluate the performance of national table tennis players by exploring the primary factors that influence their success. Coach NPC Mohd is the focus of the research. Ja’far, a skilled athlete and coach committed to nurturing future table tennis talents in Medan, North Sumatra. This study utilized a descriptive qualitative method, gathering data through in-depth interviews, direct observation of training and competitions, and documentation of accomplishments. The results showed that athletic performance is significantly impacted by physical, technical, mental, tactical, and social support factors. Sports Hall Training Facilities.